The association between pharmacy refill-adherence metrics and healthcare utilisation: a prospective cohort study of older hypertensive adults. (10th April 2019) - Dillon, Paul; Smith, Susan M; Gallagher, Paul; Cousins, Gráinne
Abstract: Aims: Methods that enable targeting and tailoring of adherence interventions may facilitate implementation in clinical settings. We aimed to determine whether community pharmacy refill-adherence metrics are useful to identify patients at higher risk of healthcare utilisation due to low antihypertensive adherence, who may benefit from an adherence intervention. Methods: We conducted a prospective cohort study, recruiting participants ( n = 905) from 106 community pharmacies across the Republic of Ireland. Participants completed a structured interview at baseline and 12 months. Antihypertensive medication adherence was evaluated from linked pharmacy records using group-based trajectory modelling (GBTM) and proportion of days covered (PDC). Healthcare utilisation included self-reported number of hospital visits (emergency department visits and inpatient admissions) and general practitioner (GP) visits, over a 6-month period. Separate regression models were used to estimate the association between adherence and number of hospital/GP visits. The relative statistical fit of each model using different adherence metrics was determined using the Bayesian information criterion (BIC). Results: For the number of hospital visits, significant associations were observed only for PDC but not for GBTM. Each 10% increase in refill-adherence by PDC was significantly associated with a 16% lower rate of hospital visits (adjusted incidence rate ratio 0.84, 95% CI 0.72–0.98, P = 0.036). Poorer adherence using both measures was associated with higher GP visits. Improvements in BIC favoured models using PDC. Conclusions: Medication refill-adherence, measured using PDC in community pharmacy settings, could be used to recognise poor antihypertensive adherence to enable effective targeting of clinical interventions to improve hypertension management and outcomes.